A 3D mesoscopic model for the closed-cell metallic foams subjected to static and dynamic loadings. (August 2015) - Fang, Qin; Zhang, Jinhua; Zhang, Yadong; Wu, Hao; Gong, Ziming
Abstract: This paper presents a three-dimensional (3D) mesoscopic model to investigate the responses of closed-cell metallic foams subjected to static and dynamic loadings, especially focusing on the 3D mesoscopic model and the mechanical response. In the first part of this paper, we propose the algorithms to generate the 3D convex polyhedrons modeling the pores with random shapes in closed-cell metallic foams. The 3D mesoscopic model of the foams and the finite element grid are proposed using the 'take & place' algorithm and the mapping algorithm. In the second part of this paper, the finite element grid is coupled into the commercial hydrocode LS-DYNA and the ALE analysis approach considering the fluid (the entrapped air) and the structure (the cell-walls) interaction is used. The plastic kinematic model and the linear polynomial equation of state are employed to simulate the cell-walls and the entrapped air, respectively. The responses of closed-cell aluminum foams subjected to static and dynamic compression at high strain rates are simulated by the proposed model and analysis approach. It is demonstrated that the simulated results agree well with test data and the entrapped air plays an important role in the responses when the foams undergo large deformation. Finally, numerical simulations are conducted using the validated approaches, focusing on the effects of mesoscopic configurations (such as the pore size, average density and cell wall strength) on the dynamic responses and the mesoscopic failure patterns. The results show that the collapse and the fracture of the cell walls behave differently under static and high strain rate loadings. Graphical abstract: Highlights: A 3D mesoscopic model of metallic foam is developed. The randomness of pores in distribution and shape is taken into account. The fracture and collapse of cell walls can be studied realistically. Mesoscale configurations of aluminum foams affect the mechanics significantly.